The Effect Of Reader’s Theater Strategy On Students’ Skills In Writing Recount Text - Kiki Rizki Amelia; Rekha Asmara; Dewi Sartika (English Education Study Program Faculty of Teacher Training and Education, 2022)
Writing is an effective tool de develop communication for students. By writing, students can explore everything to deliver to others. As a result, the purpose of this study was to look into the effect of the reader's theater strategy on improving students' writing skills when writing recount text. This was a pre-experimental study. This study's sample consisted of eighth-grade students from MTs Pidua Meranjat. The information was gathered using a written test and analyzed using a paired sample t-test. The findings revealed that the t-obtained (5.228) was higher than the t-table (0.692) at a significant level of p-value below 0.5. It meant that there was a significant improvement in writing recount text after having taught using the reader’s theater strategy. In conclusion, the Reader’s Theater strategy affected students in writing recount text because it offers a fun way of learning where students must complete a story by recreating the script by characterizing the text that was guided by its strategy.